OPTIMALISASI KRING RESERSE SATRESKRIM GUNA MENGUNGKAP TINDAK PIDANA CURANMOR DI WILAYAH HUKUM POLRES KENDAL - Nailla Zahra (Advances in Police Science Research Journal, 2022)
ABSTRACT OPTIMIZATION OF KRING RESERSE SATRESKRIM TO UNCOVER THE CRIME OF VEHICLE THEFT IN THE KENDAL POLICE JURISDICTION NAILLA ZAHRA MAHARANI, 18.254. naillazm22099@gmail.com This research discusses how to uncover the crime of theft of vehicles by optimizing one of the technical functions of criminal reserse, namely Kring Reserse, in the jurisdiction of Kendal police. Supported by data on the number of crimes (total crime) in the Kendal regency over the past three years, the crime of theft of vehicles has increased. The rise of vehicle theft cases is a concern for the author to observe and analyze more deeply how to optimize Kring Reserse, which is done by monitoring the area at some point of the crime vulnerability area. In this study, the author used problem-solving through management theory, along with the concept of optimization and the concept of Kring Reserse derived from the Hanjar Reserse Lemdiklat Polri Book in 2021. This research uses a qualitative approach so that the research carried out gets a broad picture of the problems obtained in the field. Data collection is collected by interviewing, observation, and document studies and validated through data triangulation to get valid information and data with problems that focus on the Kring Reserse Kendal police criminal reserse unit. Based on the research results that had been done by the author, several findings are found, including 1) The unavailability of SOP Kring Reserse or renewal division of duties to Kendal police criminal reserse unit personnel. 2) Lack of personnel carrying out the tasks in the field. 3) Lack of control and supervision from superiors. 4) The method used is not optimal. The author provides problem-solving steps based on the results of research that has been done, namely: 1) Coordination between Kanit and Kasat Reskrim to conduct training to all criminal reserse personnel regarding Kring Reserse activities. 2) Empower cross-functional technical functions such as Bhabinkamtibmas to carry out Kring Reserse activities. 3) The use of technology such as the Use of Zenly Applications in making it easier for Kanit to supervise and control criminal reserse personnel in Kendal Police.